OPTIMALISASI PLATFORM DIGITAL SEBAGAI INTERAKSI GLOBAL SPIRITUALITAS MELALUI PENDEKATAN SOSIAL, BUDAYA, TEKNOLOGI ERA TRANSMODERNITAS - Marbun, Ernida; Nababan, Labuan; Nasution, M. Fachrurrozi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the influence of digital platform optimization on increasing global interaction and spirituality of young men and women through a social, cultural, and technological approach in the era of transmodernity. The research method uses a mixed methods approach, including a survey of 70 respondents to obtain quantitative data, in-depth interviews with 10 respondents from the survey sample to explore deeper perspectives, and Focus Group Discussions (FGDs) with 17 cross-disciplinary experts (Christianity, Islam, culture, sociology, and digital technology) to obtain interdisciplinary validation and insights. The study also found that the era of transmodernity allows digital technology to function not only as a means of production or consumption, but as an ethical and spiritual space that brings together local and global values equally. Digital platforms can strengthen social cohesion across groups, support inclusive spiritual and cultural practices, and reduce social and cultural inequality. Based on these findings, the study recommends the development of digital platform optimization strategies, such as the design of spiritual community applications, forums for reflection on human values, and social meditation, so that they can become spaces for socially and spiritually meaningful interactions. The research output is in the form of scientific publications in Accredited National Journals, as well as being a reference for the development of digital interaction models that effectively combine technology, culture, and spirituality in the transmodern era.Keyword: culture; global interaction; digital platform; spirituality; transmodernityAbstrak: Penelitian ini bertujuan menganalisis pengaruh optimalisasi platform digital terhadap peningkatan interaksi global dan spiritualitas pemuda/i melalui pendekatan sosial, budaya, dan teknologi di era transmodernitas. Metode penelitian menggunakan pendekatan mixed methods, meliputi survei terhadap 70 responden untuk memperoleh data kuantitatif, wawancara mendalam terhadap 10 responden dari sampel survei untuk menggali perspektif lebih mendalam, serta Focus Group Discussion (FGD) dengan 17 ahli lintas disiplin (Kristen, Islam, budaya, sosiologi, dan teknologi digital) untuk memperoleh validasi dan wawasan interdisipliner. Penelitian juga menemukan bahwa era transmodernitas memungkinkan teknologi digital berfungsi bukan hanya sebagai alat produksi atau konsumsi, tetapi sebagai ruang etis dan spiritual yang mempertemukan nilai-nilai lokal dan global secara setara. Platform digital dapat memperkuat kohesi sosial lintas kelompok, mendukung praktik spiritual dan budaya yang inklusif, serta mengurangi ketimpangan sosial dan budaya. Berdasarkan temuan ini, penelitian merekomendasikan pengembangan strategi optimalisasi platform digital, seperti desain aplikasi komunitas spiritual, forum refleksi nilai kemanusiaan, dan meditasi sosial, agar dapat menjadi ruang interaksi yang bermakna secara sosial dan spiritual. Luaran penelitian ini berupa platform digital berbasis web, sekaligus menjadi referensi bagi pengembangan model interaksi digital yang memadukan teknologi, budaya, dan spiritualitas secara efektif di era transmodern.Kata kunci: budaya; interaksi global; platform digital; spiritualitas; transmodernitas.